Improving the Diagnostic Information Recorded in the Electronic Case Records in a Mental Health Service: A Quality Improvement Project - Matilda Burton; Nilamadhab Kar; Annabel Ariyathurai; Mohamed Yaasir Mohamudbucus; Vijay Perla (BJPsych Open, 2025)
Aims: Up-to-date and accurate diagnostic information is essential for many reasons including effective clinical management; however, this may not be the case for psychiatric patients seen across different healthcare settings. It was intended to explore the documentation of both psychiatric and physical diagnoses within the electronic case records (ECR), and their quality based on the character of International Classification of Diseases coding; and to update the information where appropriate.